A recombinant murine-like rotavirus with Nano-Luciferase expression reveals tissue tropism, replication dynamics, and virus transmission - Zhu, Yinxing; Sánchez-Tacuba, Liliana; Hou, Gaopeng; Kawagishi, Takahiro; Feng, Ningguo; Greenberg, Harry B.; Ding, Siyuan (Frontiers in Immunology, 2022)
Rotaviruses (RVs) are one of the main causes of severe gastroenteritis, diarrhea, and death in children and young animals. While suckling mice prove to be highly useful small animal models of RV infection and pathogenesis, direct visualization tools are lacking to track the temporal dynamics of RV replication and transmissibility in vivo. Here, we report the generation of the first recombinant murine-like RV that encodes a Nano-Luciferase reporter (NLuc) using a newly optimized RV reverse genetics system. The NLuc-expressing RV was replication-competent in cell culture and both infectious and virulent in neonatal mice in vivo. Strong luciferase signals were detected in the proximal and distal small intestines, colon, and mesenteric lymph nodes. We showed, via a noninvasive in vivo imaging system, that RV intestinal replication peaked at days 2 to 5 post infection. Moreover, we successfully tracked RV transmission to uninoculated littermates as early as 3 days post infection, 1 day prior to clinically apparent diarrhea and 3 days prior to detectable fecal RV shedding in the uninoculated littermates. We also observed significantly increased viral replication in Stat1 knockout mice that lack the host interferon signaling. Our results suggest that the NLuc murine-like RV represents a non-lethal powerful tool for the studies of tissue tropism and host and viral factors that regulate RV replication and spread, as well as provides a new tool to facilitate the testing of prophylactic and therapeutic interventions in the future.